2014
DOI: 10.4194/1303-2712-v14_1_25
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study concentrated on temporal distribution and species composition of phytoplankton connected with physicochemical variations between January 2003 and November 2004 in the South Western Caspian Sea. During the study, 75 phytoplankton were distinguished in total and average phytoplankton densities in 2003 and 2004 were 1.47×10 5 ±6.05×10 4 and 1.97×10 5 ±7.18×10 4 cells L-1 , respectively. Contributions of diatoms (66.0% in 2003; 57.0% in 2004) and cyanophytes to total phytoplankton (17.0 in 2003; 36.0% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…This fact is confirmed by active oil production on the Caspian shelf that causes contamination of seawater during transportation and pumping on oil tankers and in terminals [89]. The presented data confirm the fact that the population growth in the cities of the Caspian basin, increasing discharge of various wastewaters (industrial, agricultural and urban wastewater), development of oil production in the area, growing river navigation and eventual connection of the Caspian Sea with the World Ocean resulted in a significant increase in anthropogenic pressure on the unique ecosystem of the Caspian Sea and disturbance of its balance [90].…”
Section: Discussionsupporting
confidence: 76%
“…This fact is confirmed by active oil production on the Caspian shelf that causes contamination of seawater during transportation and pumping on oil tankers and in terminals [89]. The presented data confirm the fact that the population growth in the cities of the Caspian basin, increasing discharge of various wastewaters (industrial, agricultural and urban wastewater), development of oil production in the area, growing river navigation and eventual connection of the Caspian Sea with the World Ocean resulted in a significant increase in anthropogenic pressure on the unique ecosystem of the Caspian Sea and disturbance of its balance [90].…”
Section: Discussionsupporting
confidence: 76%
“…This survey showed that diatoms such as Thalassionema nitzschiodes and pyrrophyte Exuviaella cordata and cyanophyte Oscillatoria limosa were prevalent in Phytoplankton populations at the site. Bagheri et al (2014) showed that diatom communities were represented by a few dominant species such as D. fragilissimus and T. nitzschioides in the system.…”
Section: Discussionmentioning
confidence: 98%
“…In the Caspian Sea, various factors such as hydrological regimes, climate anomalies, increasing detergents, increasing the flow of fresh water through rivers, and increasing the level of nutrients due to the discharge of industrial and agricultural waste can affect the diversity and density of phytoplankton in coastal water of Caspian Sea (Kideys et al 2008;Bilio and Niermann 2004). Bagheri et al (2014) theorized that hydro-biological changes in the Caspian Sea, Black Sea, and Baltic Sea during the 1990s and 2000s could be definitely correlated with climatical and hydrological characters.…”
Section: Discussionmentioning
confidence: 99%